The complex refractive indices of the liquid crystal mixture E7 in the terahertz frequency range - Yang, Chan-Shan (Animo Repository, 2010)
We have used terahertz (THz) time-domain spectroscopy to investigate the complex optical constants and birefringence of a widely used liquid crystal mixture E7 in both nematic and isotropic phases (26ºC~70ºC). The extinction coefficient of E7 at room temperature is less than 0.035 and without sharp absorption features in the frequency range of 0.2~2.0 THz. The extraordinary (ne) and ordinary (no) indices of refraction at 26ºC are 1.690~1.704 and 1.557~1.581, respectively, giving rise to a birefringence of 0.130~0.148 in this frequency range. The temperature-dependent (26ºC~70ºC) order parameter extracted from the birefringence data agrees with that in the visible region quite well. Further, the temperature gradients of the THz optical constants of E7 are also determined. The optical constants of E7 in the THz or sub-millimeter wave range are found to deviate significantly from values predicated by the usual extended Cauchy equations used in the visible and near-infrared.